Накопичення важких металів деревними рослинами правобережної частини канівського природного заповідника - Семенова, К.; Тесьолкіна, Тетяна Сергіївна; Вашека, Олена Володимирівна (Київський національний університет імені Тараса Шевченка, 2024)
The problem of heavy metal pollution of the environment is very actual. Forests vegetation act as a kind of filter, cleansing the environment from harmful effects. The concentration of 11 elements (Ba, Bi, Cd, Co, Cr, Cu, Ni, Pb, Sr, Zn, Al) in soil and leaves of trees (Acer platanoides L., Aesculus hippocastanum L., Carpinus betulus L., Pinus sylvestris L., Robinia pseudoacacia L., Tilia cordata Mill., Quercus robur L.) was established. None of the species are hyperaccumulator plants, but C. betulus and A. platanoides were the most effective accumulators, having generally higher values of the biological absorption coefficient than other spesies. Lower accumulation capacity was shown by R. pseudoacacia, T. cordata, Q. robur, P. sylvestris, and A. hippocastanum. However, they have ability to accumulate certain metals (Al - for P. sylvestris, Cu - for A. hippocastanum, and Ni - for R. pseudoacacia).
Heavy metal accumulation in trees of the Kaniv Nature Reserve right bank part